2015
DOI: 10.2501/ijmr-2015-032
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Variation in Brand Growth and Decline across Categories

Abstract: This study investigates the variation in brand growth and decline across many different product categories. It uses recent consumer panel data from the UK, covering 639 brands across 28 categories, including food, personal care, home care and pet food, over a five-year period from 2008 to 2012. Consistent with the literature, the study finds that most brands in the consumer packaged goods market are stationary, as only 14% of the brands change their market share by more than three points. However, the study di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…Our study supports extant literature which shows that once the market is mature, there is little or no real change in the market at the aggregate level, despite each individual consumer purchasing propensity might still be wobbling around his/her long run steady purchasing rate (e.g. (Graham, 2009; Trinh and Anesbury, 2015)).…”
Section: Discussion Limitations and Future Researchsupporting
confidence: 88%
“…Our study supports extant literature which shows that once the market is mature, there is little or no real change in the market at the aggregate level, despite each individual consumer purchasing propensity might still be wobbling around his/her long run steady purchasing rate (e.g. (Graham, 2009; Trinh and Anesbury, 2015)).…”
Section: Discussion Limitations and Future Researchsupporting
confidence: 88%
“…There is now copious evidence that established categories of CPG brands remain in near-equilibrium over time, with little persistent trend in market share (Bass and Pilon, 1980;Dekimpe and Hanssens, 2000). Trinh and Anesbury (2015) found that most categories remain near-stationary even over five years, identifying changes in market share in excess of 3 points up or down for only 14% of brands. Dawes et al (2015) examined loyalty measures (switching, SCR and average repertoire size) in 26 UK and US categories in periods ranging between six and thirteen years and found very little evidence for declining (or, for that matter, increasing) behavioural loyalty.…”
Section: Systematic Dirichlet Deviationsmentioning
confidence: 99%
“…This law has been extensively tested over thirty-five years or more, and rightly so, since it provides a key to the multi-million dollar question of how brands grow. When Double Jeopardy constrains choice behaviour, marketers should know that brand share growth depends on substantially increasing the size of the customer base rather more than on managing customer loyalty (Sharp, 2010; Trinh and Anesbury, 2015).…”
Section: Introductionmentioning
confidence: 99%